The complete chloroplast genome sequence of Rehmannia glutinosa (Gaertn.) DC. Wild. (Rehmannia) - Yang, Hao (Mitochondrial DNA B Resour, 2021)
In this study, we constructed and annotated a complete circular chloroplast genome of wild R. glutinosa. The chloroplast genome of wild R. glutinosa is 153,678 bp in length, including two inverted repeat (IR) regions of 25,759 bp, separated by a large single copy (LSC) region of 84,544 bp and a small single copy (SSC) region of 17,616 bp. The genome contains 149 genes, including 104 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Neighbor-joining method phylogenomic analysis showed that wild R. glutinosa formed a monophyletic group, and was sister to other groups of R. glutinosa.